Canine Mesenchymal Stromal Cell-Mediated Bone Regeneration is Enhanced in the Presence of Sub-Therapeutic Concentrations of BMP-2 in a Murine Calvarial Defect Model - Dobson, Lauren K.; Zeitouni, Suzanne; McNeill, Eoin P.; Bearden, Robert N.; Gregory, Carl A.; Saunders, W. Brian (Frontiers in Bioengineering and Biotechnology, 2021)
Novel bone regeneration strategies often show promise in rodent models yet are unable to successfully translate to clinical therapy. Sheep, goats, and dogs are used as translational models in preparation for human clinical trials. While human MSCs (hMSCs) undergo osteogenesis in response to well-defined protocols, canine MSCs (cMSCs) are more incompletely characterized. Prior work suggests that cMSCs require additional agonists such as IGF-1, NELL-1, or BMP-2 to undergo robust osteogenic differentiation in vitro. When compared directly to hMSCs, cMSCs perform poorly in vivo. Thus, from both mechanistic and clinical perspectives, cMSC and hMSC-mediated bone regeneration may differ. The objectives of this study were twofold. The first was to determine if previous in vitro findings regarding cMSC osteogenesis were substantiated in vivo using an established murine calvarial defect model. The second was to assess in vitro ALP activity and endogenous BMP-2 gene expression in both canine and human MSCs. Calvarial defects (4 mm) were treated with cMSCs, sub-therapeutic BMP-2, or the combination of cMSCs and sub-therapeutic BMP-2. At 28 days, while there was increased healing in defects treated with cMSCs, defects treated with cMSCs and BMP-2 exhibited the greatest degree of bone healing as determined by quantitative μCT and histology. Using species-specific qPCR, cMSCs were not detected in relevant numbers 10 days after implantation, suggesting that bone healing was mediated by anabolic cMSC or ECM-driven cues and not via engraftment of cMSCs. In support of this finding, defects treated with cMSC + BMP-2 exhibited robust deposition of Collagens I, III, and VI using immunofluorescence. Importantly, cMSCs exhibited minimal ALP activity unless cultured in the presence of BMP-2 and did not express endogenous canine BMP-2 under any condition. In contrast, human MSCs exhibited robust ALP activity in all conditions and expressed human BMP-2 when cultured in control and osteoinduction media. This is the first in vivo study in support of previous in vitro findings regarding cMSC osteogenesis, namely that cMSCs require additional agonists to initiate robust osteogenesis. These findings are highly relevant to translational cell-based bone healing studies and represent an important finding for the field of canine MSC-mediated bone regeneration.